Human resource accounting (HRA) disclosure of Bangladeshicompanies and its association with corporate characteristics - Al Mamun, Syed Abdulla (BRAC University, 2010)
This study reports the relationship between corporate characteristics and Human Resource Disclosure (HRAD) level in fifty five randomly selected companies of Bangladesh. The relationships were determined using a HRAD Index (HRADI) under a number of hypotheses. The results of the study show that companies averagely disclose 25% of the total HRAD items. In this study, HRAD has been found significantly related with the size of the company, category of the company (financial or non-financial) and profitability. However, HDAD had no influence on the age of companies.